PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA PT. PLN (PERSERO) ULP TANJUNG KARANG - Dwi Khafifah; Toton Toton; Hasbullah Hasbullah (Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the effect of competence and motivation on employee performance at PT. PLN (Persero) ULP Tanjung Karang. The main source for the success of the task in an effort to increase work productivity. The respondents of this research were all employees of PT. PLN (Persero) ULP Tanjung Karang, totaling 30 respondents. Data collection using SPSS version 25.0. Based on the results of the discussion obtained multiple linear regression equations. The coefficient of determination test is 0.417. The test results show that competence has a significant effect on employee performance, motivation has a significant effect on employee performance with the f test results at a significant level of 0.000 simultaneously showing competence and motivation have a positive and significant effect on employee performance.